The Mexican Government's Educational Policy since 1992 - Pablo Latapí Sarre (Universidad Autónoma de Baja California, 2004)
The paper deals with four of the Mexican government' educational policies derived from the National Accord to Modernize Basic and Normal Education (Acuerdo Nacional para la Modernización de la Educación Básica y Normal -ANMEB-) signed in may, 1992. These are: the decentralization of basic education; curricular renovation and the production of textbooks and educational material; reforms to teachers' working conditions; and society's participation in education. The study was done by means of documentary research and interviews with the Department of Education's head officials. Among the main findings are: the continuity of consensus between the federal and the states governments; the promotion of the states' initiatives in substantive subjects by the Department of Education and the acknowledgement of limitations encountered in basic education caused by the predominance of the central federal power; the qualitative innovations in textbooks and educational material; the postponement of pre-school and secondary education reforms; the great unbalance of teachers' initial education; the high degree of endogamy and political fiefs within the teachers' community; the wide variety of projects at different levels and institutions to promote parents' participation in schools and to make principals and teachers sensitive to such participation.